Pengaruh Ekstrak Daun Sirih Merah (Piper crocatum) Terhadap Profil Darah Dan Kelulushidupan Ikan Mas (Cyprinus carpio) Yang Diinfeksi Bakteri Aeromonas hydrophila - Syahida, Intan Eska Amalia; Sarjito, Sarjito; Prayitno, Slamet Budi; Lusiastuti, Angela Mariana (Journal of Aquaculture Management and Technology, 2013)
The study aimed was to know the influence of Piper crocatum exstract on the blood profile included total erythrocyte, total leukocyte, differential leukocyte (DL), phagocytosis indeks (IF) and survival rate of common carp (Cyprinus carpio) infected by Aeromonas hydrophila and the best concentration of P. crocatum for imunostimulatory common carp of infected A. hydrophila. The research was conducted at Research and Development of Freshwater Aquaculture, Bogor. The methods used in this research is experimental methods by using random design complete (RAL) with 4 treatments and three replicates. The research was conducted at Research and Development of Freshwater Aquaculture, Bogor. The treatments of different addition of P. crocatum exstract on fish feed, 0 gr/kg feed (treatment A), 5 gr/kg feed (treatment B), 10 gr/kg feed (treatment C), 15 gr/kg feed (treatment D). The treatnent was given 21 days. The research results obtained additional P. crocatum exstract significantly different effect (P0,05) on percentage of netrofil (2%) and survival rate of common carp (C. carpio) infected by A. hydrophila (40%), the best concentration of P. crocatum on feed for immunostimulant common carp of infected A. hydrophila, the result showed the best dose 5 g/kg feed